American detective - Estleman, Loren D. (Estleman, Loren D. Amos Walker novels., 2007)
Hardboiled detective Amos Walker returns for his nineteenth outing in his most challenging case yet. Former Detroit Tigers pitcher Darius Fuller wants Walker to break off his daughters engagement to Hilary Bairn, a man Fuller believes is after her two million dollar trust. Walker breaks into Bairns apartment, only to be ambushed by cops. A murder has taken place, and the victim is Fullers daughter. Walker and the cops assume that Bairn is the murderer, but Walker has no idea what he is getting into. Walker is led to a meeting with a casino owner, who tells him Bairn owed money to a loan shark. The loan shark tells Walker that he is not the only one after Bairn. Soon Walker finds himself on the run from crooked cops and vile gangsters. Every time Walker thinks hes solved the case, he finds out he is further from the truth than when he started. This case will take all of Walkers cunning, and will prove to be his greatest trial ever!